Acute Adrenal Insufficiency in the Perioperative Period: A Case Report. Issue 3 (1st February 2019) - Karamchandani, Kunal; Leathem, Jarrett; Sinz, Elizabeth H.
Abstract : Acute adrenal insufficiency is a rare but potentially life-threatening event during the perioperative period. The usual manifestations of an acute adrenal crisis can mimic common postoperative complications and a high index of suspicion is required for the diagnosis. Early diagnosis and prompt treatment can be lifesaving. We present the case of a 65-year-old man who, after a partial nephrectomy, developed acute adrenal insufficiency, which remained undiagnosed in the postoperative period, eventually leading to cardiac arrest. This case highlights the need for perioperative physicians to have a watchful eye for diagnosing and treating this uncommon yet lethal condition.